(untitled) (Archives of Criminology, 2023)
This article will examine the efficacy of current programme services for adolescent girls at risk of forced labour through an analysis of Walk Free’s Promising Practices Database. The Database is a collection of evaluations of anti-slavery and counter-trafficking programmes since 2000, categorised by type of intervention, location of programme, and target population, among other terms. This article identifies what lessons can be learnt, if any, to both prevent and tackle the forced labour of adolescent girls, with a particular focus on the garment and textile industries. We examine a subset of the Promising Practices Database of 81 evaluations, where at least one component in programme design was targeted at adolescent girls. We find that, in line with other critiques of human trafficking research, most evaluations are disproportionately focussed on programmes tackling sex trafficking to the exclusion of other forms of forced labour. Based on two existing evaluations, and related programmes in the garment sector, we determine the importance of community-led, inclusive, rights-based awareness-raising and the need to tailor interventions specifically to the needs and life-stage of the target group.